Revisiting the Importance of Non-Tradable Goods' Prices in Cyclical Real Exchange Rate Fluctuations - Ida Wolden Bache; Kjersti Næss; Tommy Sveen (Norges Bank, 2009)
In an influential paper Engel (1999. Accounting for U.S. Real Exchange Rate Changes, Journal of Political Economy 107, 507-538) argues that essentially all the fluctuations in the real exchange rate can be attributed to fluctuations in the relative price of traded goods, and that only a small part of the fluctuations can be attributed to changes in the relative price of non-tradables. We instead decompose the real exchange rate into three components: the relative price of traded goods at-the-dock, the difference in the relative price of non-traded to traded goods and the difference in the wedge between retail prices of traded goods and the prices of traded goods at-the-dock. Using data on US bilateral real exchange rates we find that the fluctuations in the relative wedge between retail prices and traded goods prices at-the-dock account for on average between 30 and 70 percent of the movements in the real exchange rate. These findings suggest that the relationship between traded goods prices at-the-dock and retail prices of traded goods is key to understanding real exchange rate fluctuations.
hdl:11250/2497642
Keywords: F31; F41; 330; real exchange rates